Pengaruh Kemudahan Penggunaan, Keamanan, dan Keandalan Terhadap Penggunaan Mobile Banking dikalangan Masyarakat - Ulfa Arsita; Rifqa Ayu Dasila; Indah Pratiwi; Arsita, Ulfa (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Currently the banking sector provides product services in the form of electronic banking for customers, one of which is mobile banking. Mobile banking is a banking service that allows customers to make various financial transactions through mobile devices, such as smartphones or tablets. This study aims to examine the influence of ease of use, security, and reliability on the use of mobile banking among the people of Palopo city. Data was collected using a questionnaire that was distributed online to respondents. This study uses a quantitative method. The sample was taken using the purposive sampling technique with a total of 105 respondents collected. To process the data in this study, the Statistical Package for Social Science (SPSS) program is used. The results of this study show that ease of use, security, and reliability have a significant effect on the use of mobile banking.